Famílias em situação de imigração com crianças: acolhimento nos serviços de saúde do sistema único de saúde - Farias, Bruna Luana de Souza (Universidade Federal de São Carlos, 2025)
Currently, international migration is understood to be a social determinant of health, as this phenomenon involves processes that tend to increase social and health inequities, especially when intertwined with social markers such as race, gender, and class, hindering access to health services. There is an intense migratory flow in Brazil, and children and families are part of these displacements; therefore, it is fundamental to welcome families and the perspectives and choices of children, so that their priorities, beliefs, and knowledge are considered in the planning and provision of care, for the construction of health services in various scenarios and health levels. Brazil is a country marked by the xenophobia inherent in its history of slavery; thus, health services frequently produce and reproduce violence against immigrants and their families. Given this scenario, the following question arises: How are immigrant families with children served in public health services? Objective: To understand the perception of immigrant families with children who are served in Brazilian public health services. Material and method: This is an exploratory qualitative study, whose data collection used semi-structured interviews with five families of immigrants residing in the cities of São Paulo and São Carlos, between June and July 2024. All material was transcribed and analyzed using Thematic Analysis. Results: Six categories emerged: 1- The complexity of migratory adaptation and its implications for health. 2- Experiences of prejudice, discrimination, and xeno-racism in the context of health. 3- Barriers to reception: communication and bureaucratic challenges. 4- Access to and quality of health care: between right and reality. 5- The role of children in health care: children as a protective factor against discrimination. 6- Coping strategies and resilience of immigrants. Final considerations: This study showed that the experiences of these families in Brazil, especially in the context of health, are marked by structural inequalities expressed in the confluence of nationality, race, gender, class, education, linguistic proficiency, citizenship/documentation status, length of residence in the country, and cultural differences. The interaction between these markers creates a dynamic that generates not only limitations in access to and reception in services, or barriers for people in immigration situations, but also constitutes an expression of necropower, determining which lives are considered more or less worthy of care in health spaces.
Families in immigration situation with children: reception in the health services of the public health system
Keywords: Crianças; Família; Imigração; Acolhimento; Acesso universal à saúde; Interseccionalidade; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::COMPONENTES DA DINAMICA DEMOGRAFICA::MIGRACAO; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; 3. Saúde e Bem-Estar; 10. Redução das Desigualdades